Prediction of water and wastewater networks rehabilitation based current age and material distribution - Malm, A.; Svensson, G.; Bäckman, H.; Morrison, Gregory (2013)
Ageing drinking water, stormwater and sewer pipe networks imply an increased degree of rehabilitation. The need for rehabilitation can be predicted using lifetime distribution functions together with current network age and material distribution. In Sweden, current age and material distribution is neither documented on a national level, nor for many water utilities on a local level. In this study, current network age and material distribution was provided through a questionnaire sent to Swedish water and wastewater utilities and the data provided were extrapolated to cover the whole of Sweden. The data were then combined with lifetime distribution functions to provide predictions. One limitation is that for newer materials the lifetime is still uncertain. Predictions were made for different scenarios to reflect local differences and the medium scenario shows that while the Swedish rehabilitation rate is stable, investments in monetary terms need to double in the next 60 years. The rehabilitation rate is also dependent on the extent to which the network is expanded. This method can be used to calculate national investment needs, and the results can also provide a basis for estimates for Swedish utilities with data scarcity. © IWA Publishing 2013.